Affective Pragmatism: Political Memory, Emotions, and Indonesia's Selective Humanitarianism in Refugee Governance - Atin Prabandari; Balya A. Segara; Emma Seruni Ketaren (Nation State: Journal of International Studies, 2026)
This article explores Indonesia’s ambivalent approach to refugee governance through the concept of “Affective Pragmatism.” This concept addresses the tension, which is not accidental but structural, between emotion-driven humanitarian commitments and fear-based concerns regarding border security. While the 1951 Refugee, Convention calls for universal protection, Indonesia promotes humanitarian diplomacy, at the regional level through the Bali process, while maintaining tight control over domestic asylum policies. Drawing on constructivist and postcolonial theory, this article seeks to demonstrate how political memory, particularly the legacy of the 1955 Bandung Conference, has shaped Indonesia’s affective response to various humanitarian crises. In this article, the Rohingya are incorporated into a shared narrative of empathy and postcolonial trauma, while other illegal migrants face indifference and rejection. By linking affective pragmatism to debates on the contestation of norms and the politics of exclusion, this article offers a framework for understanding how emotions and memory create an uneven landscape of protection and contribute to the evolving debate on refugee governance in Global South countries, including Indonesia.